Physiological and psychological changes caused by archery athletes monitoring their own heartbeat in shooting situation, and the effects on performance - Takai, H.; Saijyo, O.; Kusumoto, Y. (Japanese Journal of Sport Psychology, 2009)
The purpose of this research was to investigate the psychological and physiological effects, and the effects on performance, of archery athletes monitoring their own heartbeats in shooting situations. Two conditions were used for the experiment: (1) control condition, in which athletes competed without hearing their own heartbeats; and (2) experimental condition, in which athletes competed while listening to their own heartbeats. The two conditions were compared using the following indices: (1) VAS (Visual Analogue Scale) as a psychological index; (2) electrocardiogram R-R interval as a physiological index; and (3) shooting time, shooting timing, and score as indices of performance. The results of the experiment were as follows: (1) No significant differences in mood between the control condition and the experimental condition were observed. (2) In both the control condition and the experimental condition, the electrocardiogram R-R interval grew shorter from pre-experiment rest to the experimental period. (3) Athletes who monitored their own heartbeat showed less variation in shooting time than those in the control condition. (4) Athletes who monitored their own heartbeat fired more shots during the ventricular diastole than during the ventricular systole in comparison to those in the control condition. (5) Athletes who monitored their own heartbeat scored higher than those in the control condition. These results indicate that monitoring the heartbeat during shooting reduced fluctuations in shooting time, increased the number of shots during the ventricular diastole, and gave higher scores; it would therefore appear that monitoring the heartbeat during shooting is a valid method for enabling athletes to deliver high performance.